Rendimiento del maíz según manejo de la parte aérea de la planta - Pinchinat, A.M. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
In five varities of maize, grain yield was measured, as affected by the removal of different amounts of leaves and stem from the plant at the full dent stage, a practice intended to facilitate intercropping. Grain yield (3.1 1(10´kg) / ha), as obtained form the check treatment (M1) in wich no aerial plant part was removed, was not significantly reduced (97 per cent of check) by removing the leaves below the ear (M2). On the other hand grain yield was significantly reduced (77 per cent of check) by removal of the leaves and stem above the ear (M3) or by the combination of M2 and M3 (M4). Incidental forage production (t/ha) varied form 2 2 in M2 to 10 1 in M4.